Towards a policy for early childhood education in Latin America and the Caribbean - Reimers, Fernando (Academy for Educational Development, 1992)
This paper was intended to stimulate debate about the need for national policies of early childhood education in Latin America and the Caribbean (LAC), by arguing that each country should have a set of policies that give early childhood education the importance it deserves as an arena for promoting human and social development. The paper reviews research conducted in the United States, the LAC region, and other countries indicating that high quality preschool programmes can benefit children by improving their nutrition, helping them develop basic cognitive skills, and inculcating in them, at an early age, intellectual curiosity and the desire to learn. The paper recommends that, because the key constraint to establishing successful preschool programmes in the LAC region is the lack of financial resources, LAC countries should develop methods to attract private sector participation to achieve the goal of providing high-quality preschool programmes for all children who need them. It suggests that governments might also develop partnerships with other nongovernmental organizations (NGOs) and local communities to provide quality care for poor children
Keywords: Early childhood care and education